THE ROLE-PLAY FOR CHILD CARE IN FAMILIAL ENTREPRENEUR IN ENREKANG REGENCY - Suparman (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
The main problem in this study is how the pattern of parenting children in the family of traders and how the pattern of parenting is applied in the family of traders to support the development of children's talents. The purpose of this study is to find out how the behavior patterns of parents in raising children, knowing what values ​​children get from parenting, and how children act in society. The location of this research is in Lewaja Village, Enrekang Regency because this location is found by many traders. The type of this research is descriptive qualitative. Data collection techniques used are in-depth interviews, observation, and documentation. The sampling technique used the purposive sampling technique. The data analysis technique used is the interactive model analysis that uses three main components, namely data reduction, data presentation, and concluding. In summary, the results of this study are that the role of parents has not been fully implemented properly, because there are still many parents who give their roles to other institutions, this is done due to several considerations because many parents cannot fully supervise their children because they are busy making a living. But some parents teach their education to their children because there are parents who want to play a direct role in shaping the role of children's development. Based on the results of the study, it can be concluded that directly or indirectly, parents have a very large role in shaping the character and personality values ​​of children.